The impact of heavy-quark loops on LHC dark matter searches - Haisch, U; Kahlhoefer, F; Unwin, J (2012)
If only tree-level processes are included in the analysis, LHC monojet searches give weak constraints on the dark matter-proton scattering cross section arising from the exchange of a new heavy scalar or pseudoscalar mediator with Yukawa-like couplings to quarks. In this letter we calculate the constraints on these interactions from the CMS 5.0/fb and ATLAS 4.7/fb searches for jets with missing energy including the effects of heavy-quark loops. We find that the inclusion of such contributions leads to a dramatic increase in the predicted cross section and therefore a significant improvement of the bounds from LHC searches.